2020
DOI: 10.3390/ijms21041263
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity Influences VEGF, MAPK, and PAM Signaling in Prostate Cancer Cells

Abstract: Prostate cancer is one of the leading causes of cancer mortality in men worldwide. An unusual but unique environment for studying tumor cell processes is provided by microgravity, either in space or simulated by ground-based devices like a random positioning machine (RPM). In this study, prostate adenocarcinoma-derived PC-3 cells were cultivated on an RPM for time periods of 3 and 5 days. We investigated the genes associated with the cytoskeleton, focal adhesions, extracellular matrix, growth, survival, angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 99 publications
(145 reference statements)
3
49
0
Order By: Relevance
“…13,14 The PI3K-Akt signaling pathway can further upregulate the MAPK and VEGF signaling pathways, which can lead to cell proliferation and angiogenesis. 15,16 Our data showed that integrin alpha 11 significantly increased in the AH of PDR subjects and may initiate the development of PDR.…”
Section: Pi3k-akt Signaling-related Pathwaysmentioning
confidence: 63%
See 1 more Smart Citation
“…13,14 The PI3K-Akt signaling pathway can further upregulate the MAPK and VEGF signaling pathways, which can lead to cell proliferation and angiogenesis. 15,16 Our data showed that integrin alpha 11 significantly increased in the AH of PDR subjects and may initiate the development of PDR.…”
Section: Pi3k-akt Signaling-related Pathwaysmentioning
confidence: 63%
“…15,16,23 HIF-1 responds to hypoxia and upregulates the vascular endothelial growth factor (VEGF) signaling pathway. 15,16 In turn, VEGF initiates the mitogen-activated protein kinase (MAPK)signaling pathway, resulting in cell proliferation and angiogenesis. 15,16 Overall, our pathway analysis and literature review enabled us to generate a novel biological process map for the development of PDR (Fig.…”
Section: Novel Biological Process Map Based On Our Proteomic Datamentioning
confidence: 99%
“…The PI3K/Akt pathway regulates cell survival, proliferation, and motility. The PI3K-Akt pathway has been indicated in participating in eNOs production and inhibition of apoptosis in SMG exposed-cells ( Shi et al, 2012 ; Ferranti et al, 2014 ; Arun et al, 2017 ; Hybel et al, 2020 ). In the present study, it was confirmed that the p-AKT and p-PI3K protein, phosphorylated forms of PI3K and Akt, were enhanced along with the time of exposure to SMG which indicated that the concomitant survival signal was also activated when CVEC apoptosis was triggered under SMG.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that Lewis y modi ed HE4 promotes the chemotherapy-resistant biological behaviors of ovarian cancer through the p38MAPK signaling pathway. We then constructed a PPI network, using the MCC and MCODE algorithms, and identi ed four hub genes among the overlapped genes (VEGFA, EGR1, HIF1A, and PTGS2); analyzing the known functions of these genes can provide ideas and breakthroughs for prospective studies on HE4 and Lewis y. VEGF-mediated MAPK/ERK and PI3K/AKT signaling pathways play an important role in regulating the growth, proliferation, migration, and angiogenesis of tumor cells and vascular endothelial cells 36 ; moreover, VEGFA has a known role in regulating tumor cell chemotherapeutic drug sensitivity, In addition to its important function in reproductive health 37,38 . EGR1 is bidirectional regulator of pathological process in malignant tumors; in breast cancer and lung cancer tissues, the EGR1 down-regulation plays a tumor-suppressive role and inhibits the proliferation and migration of tumor cells 39,40 ; whereas, in colorectal and prostate cancers, EGR1 plays an oncogenic role where its signi cant up-regulation promotes the proliferation and migration of tumors 41,42 .…”
Section: Discussionmentioning
confidence: 99%